2008
DOI: 10.1002/hep.22216
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant factor VIIa for variceal bleeding in patients with advanced cirrhosis: A randomized, controlled trial

Abstract: on behalf of the International Study Group on rFVIIa in UGI Hemorrhage A beneficial effect of recombinant activated factor VII (rFVIIa) in Child-Pugh class B and C patients with cirrhosis who have variceal bleeding has been suggested. This randomized controlled trial assessed the efficacy and safety of rFVIIa in patients with advanced cirrhosis and active variceal bleeding. At 31 hospitals in an emergency setting, 256 patients (Child-Pugh > 8; Child-Pugh B ‫؍‬ 26%, C ‫؍‬ 74%) were randomized equally to: placeb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
157
1
9

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 284 publications
(170 citation statements)
references
References 32 publications
3
157
1
9
Order By: Relevance
“…Previous observations are in line with the long lasting evidence that the PT is a poor predictor of peri-or post-operative bleeding in cirrhosis [15][16][17][18][19][20][21][22]. Furthermore, a powerful pro-hemostatic agent, such as recombinant activated factor VII (rFVIIa), although capable of considerably shortening the PT [23], proved to be ineffective to stop esophageal bleeding [23,24], or to reduce bleeding at surgery [25,26].…”
Section: Prothrombin Timementioning
confidence: 62%
See 2 more Smart Citations
“…Previous observations are in line with the long lasting evidence that the PT is a poor predictor of peri-or post-operative bleeding in cirrhosis [15][16][17][18][19][20][21][22]. Furthermore, a powerful pro-hemostatic agent, such as recombinant activated factor VII (rFVIIa), although capable of considerably shortening the PT [23], proved to be ineffective to stop esophageal bleeding [23,24], or to reduce bleeding at surgery [25,26].…”
Section: Prothrombin Timementioning
confidence: 62%
“…rFVIIa promotes hemostasis by binding to the surface of platelets activated at sites of vascular injury, and by directly activating factor X [24,119,120]. In patients with and without liver diseases, administration of rFVIIa shortened the abnormal PT value [119][120][121][122][123][124].…”
Section: Recombinant Activated Factor VIImentioning
confidence: 99%
See 1 more Smart Citation
“…One study found that when analyzed at different laboratories, the use of different PT reagents and laboratory equipment at different laboratories was found to account for a 26% difference in INR values from the same individuals with cirrhosis [13]. Given a tenuous balance of a disrupted procoagulatant and anticoagulant factor synthesis in liver disease, increasing INR values may reflect worsening synthetic function of the liver, but does not necessarily reflect a higher propensity for bleeding events and only reflects the procoagulant side of this balanced equation [14]. Lowering or normalizing INR values in patients with bleeding events, such as variceal bleeding, does not lead to improved outcomes or decreased failure rates in hemorrhage control [15].…”
Section: Discussionmentioning
confidence: 99%
“…Actually, the 6-week mortality rate due to variceal bleeding is 15-20%, and in patients with severe decompensated cirrhosis, the mortality rate increases up to 30%. [6][7][8] The authors did not describe the bleeding or re-bleeding rate during follow-up, although variceal bleeding was one of the main reasons of death in that study. As mentioned in the paper, PPI was given to patients without strong indications (epigastric pain, nausea or vomiting).…”
Section: Acknowledgementmentioning
confidence: 97%